Lancement d’un projet de centrale solaire à Guerrara (El Watan, 2025)
Le ministre de l’Energie et des Energies renouvelables, Mourad Adjal, cité par l’APS, a lancé, hier à Guerrara (wilaya de Ghardaïa), la réalisation d’une centrale solaire de 82 ...
Keywords: Développement durable -- Mzab

Campagne nationale de reboisement : De vastes opérations de boisement lancées dans le Sud (El Watan, 2025)
Des campagnes massives de reboisement ont été lancées dans plusieurs wilayas à l'occasion de la Journée nationale de l'arbre. AOuargla, la cérémonie officielle du coup d'envoi a été ...
Keywords: Développement durable -- Mzab

اوران: مشروع مقترح لتنظيم الكفارات وتعزيز التكافل الاجتماعي - بن يحى, علي صالح; بابا وموسى, محمد أحمد (دار نزهة الآلباب, 2022)
Keywords: Développement durable -- Mzab

Implementing Sustainability in Urban Desert Regions Through Solar Orientation, The Islamic Vernacular Architecture of the M'zab Ksour in Particular - Dahmani, Krimo; Aouissi, Khalil Bachir; Chettah, Saif Eddine (Journal of Islamic Architecture, 2024)
This study investigates the role of solar orientation in creating sustainable urban land systems in desert regions, using the Ksour of M'Zab in Algeria as a case study. The Ksour are vernacular Islamic and millenarian cities inhabited for centuries, and their urban design has evolved to respond to extreme climatic conditions, particularly insolation. Through a geometric analysis of the road system, this study demonstrates how the optimal orientation of urban lanes ensures the integration of extreme climatic conditions and creates comfortable streets for pedestrians. The study compares two old Ksour (El Atheuf and Beni Yezguen) with a new Ksar (Tafilalet) and statistically evaluates their solar orientation. The results show that solar orientation is a crucial tool for understanding the sustainability of desert cities. Thus, traditional knowledge and contemporary design practices can be integrated to create sustainable urbanism in arid environments. This study contributes to the growing body of knowledge on sustainable architecture by providing insights into how traditional knowledge can create resilient cities in challenging environments and promote sustainable development.
Keywords: Développement durable -- Mzab

Citizen science project in the M’zab valley oases (Algeria): Making groundwater management visible to young generations through the participatory visual approach - Hamamouche, Meriem Farah; Saidani, Mohamed Amine; Fantini, Emanuele (Copernicus Meetings, 2024)
Keywords: Développement durable -- Mzab

Centre de développement des énergies renouvelables Ghardaia - Babanedjar, Younes (Université de Blida, 1991)
Keywords: Développement durable -- Mzab

Ghardaïa : les particularités d'une cité et l'apport du développement - Belkhodja, Amar (El Moudjahid, 1977)
Keywords: Développement durable -- Mzab

Ghardaïa, pour un développement durable - Benachenhou, Abdellatif; Benachenhou, Yacine (Editions Alpha, 2011)
Keywords: Développement durable -- Mzab